Comprehensive investigation of an in-hospital transmission cluster of a symptomatic SARS-CoV-2–positive physician among patients and healthcare workers in Germany. (3rd October 2020) - Wendt, Ralph; Nagel, Stephan; Nickel, Olaf; Wolf, Johannes; Kalbitz, Sven; Kaiser, Thorsten; Borte, Stephan; Lübbert, Christoph
Abstract: We investigated potential transmissions of a symptomatic SARS-CoV-2–positive physician in a tertiary-care hospital who worked for 15 cumulative hours without wearing a face mask. No in-hospital transmissions occurred, despite 254 contacts among patients and healthcare workers. In conclusion, exposed hospital staff continued work, accompanied by close clinical and virologic monitoring.